Microstructure tailoring of a wire-arc DED processed Ti6242 alloy for high damage tolerance performance - Zakir, Farhana; Syed, Abdul Khadar; Zhang, Xiang; Davis, Alec E.; Sahu, Vivek K.; Caballero, Armando E.; Biswal, Romali; Prangnell, Philip B.; Williams, Stewart W. (Elsevier, 2025)
This paper examines the effects of interpass hammer peening and post-process β annealing on the tensile properties, high-cycle fatigue, and fatigue crack growth behaviour of the titanium alloy Ti-6Al-2Sn-4Zr-2Mo-0.1Si (Ti6242), processed via wire-arc directed energy deposition (w-DED, also known as WAAM). A major challenge in additive manufacturing of titanium alloys is the development of a coarse columnar grain structure under standard build conditions, leading to significant anisotropy and variability in mechanical properties. This study demonstrates that interpass peening effectively refines the grain structure by inducing recrystallization, resulting in isotropic properties and increased strength without compromising fatigue crack growth resistance. Additionally, post-deposition annealing above the β-transus temperature (β annealing) significantly reduces the fatigue crack growth rate by an order of magnitude through microstructural refinement. The formation of coarse single-variant lamellar colonies promotes crack path branching and deviation, enhancing fatigue crack growth performance. Combining in-process grain refinement via peening with post-process β annealing further increases the threshold stress intensity factor by 2.5 times. These improvements provide substantial benefits for damage-tolerant design principles.
Keywords: 40 Engineering; 4016 Materials Engineering; 4014 Manufacturing engineering; 4016 Materials engineering; Additive manufacturing; WAAM; Hammer peening; Fatigue crack growth; Titanium alloys